PENGARUH FORMULASI BAHAN EDIBLE COATING DAN LAMA PENYIMPANAN TERHADAP RESPON BUAH TOMAT (SOLANUM LYCOPERSICUM L.) DI SUHU PENDINGINAN (Lycopersicon esculentum Mill) - Yudi Garnida; Yusman Taufik; Yelliantty Yelliantty (Jurnal Penelitian Pendidikan IPA, 2022)
Post-harvest handling of horticultural products is very influential on product quality, because storage temperature is one of the important factors to maintain product quality, especially fresh fruits and vegetables. The purpose of this study were to determined the effect of calcium chloride concentration (CaCl2) and starch type as edible coating material against inhibition of chilling injury of tomato. The research method were carried in two stages, namely the preliminary research and main research. The preliminary research was conducted to determine the temperature and time of starch drying.Â  The main research using Randomized Block Design (RAK) method with 3x4 factorial with 2 replications. The first factor was chloride calcium concentration consisting of 3 levels of a1 (1%), a2 (2%) and a3 (3%). The second factor is type of starch as edible coating material which consists ogf 4 levels of b1 (without edible coating), b2 (sweet potato starch), b3 (cassava starch) and b4 (ganyong starch). The main research responses include chemical responses (vitamin C and total soluble solid), physical responses (weight loss and firmness), and organolptic reponses (color and appearance). Preliminary research results were obtained the temperature of 60 Â° C and the best 5 hours for starch drying. The main research results showed that the concentration factor of calcium chloride (A) affected the color and appearance either on day 5 or day 10. The type of starch as an edible coating material (B) had an effect on vitamin (C) content, total soluble solid, color and appearance on day 5 and day 10. Factor interaction of calcium chloride concentration and type of starch as edible coating material influenced to shrinkage oweight, color and appearance on day 5 and day 10. Ganyong starch has better results based on the response of vitamin C, total soluble solid and weight loss.